Arthur goes to camp - Brown, Marc Tolon (Boston : Little, Brown, 1982)
Arthur is not looking forward to Camp Meadowcroak, and when mysterious things start happening there, he decides to run away.
2.7
K-3
380
Accelerated Reader AR
Keywords: Camping -- Fiction; Camps -- Fiction; Animals -- Fiction